Particulated microalgae composite (PMC) as substitute for live microalgae in culture of juvenile Manila clam Ruditapes philippinarum (A. Adams and Reeve, 1850): A feasibility analysis - Liang, Jian; Bi, Xiangdong; Dai, Wei; Deng, Yuewen (Indian Journal of Fisheries, 2021)
To evaluate the feasibility of particulated microalgae composite (PMC) as live microalgae substitute in artificial breeding of Manila clam Ruditapes philippinarum, effects of replacing Dicrateria inornata with partial or total PMC on the growth, digestive enzyme activities, nutritional ingredient composition and microbial composition in faeces of juvenile clams were investigated. The results showed that 50 and 100% PMC replacement did not affect the mean shell length, mean body weight and survival rate of juvenile clams (p>0.05). Juvenile clams fed with 100% PMC replacement had higher lipase and pepsin activities than those fed with 100% D. inornata (p